2012
DOI: 10.1111/j.1445-5994.2012.02741.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in liquid emptying in migraine patients: diagnosed with liquid phase gastric emptying scintigraphy

Abstract: Gastric stasis is suspected mostly to be encountered during acute migraine attack. The aim of this study is to evaluate the liquid phase gastric emptying and motility in migraine patients in ictal and interictal periods in comparison to normal subjects with gastric emptying scintigraphy. Seven women with migraine and age, sex matched controls who applied to the Neurology Department from May 2009 to May 2010 were compared. Gastric emptying study with a standard liquid was performed one time in the non‐migraineu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…In addition, migraine patients during the interictal period, had delayed gastric stasis compared with during the ictal period 21. However, previous studies had the limitation of not evaluating gastrointestinal symptoms during the interictal period and thus showed controversial results 20-22. Therefore, in our study we enrolled subjects with migraine without gastrointestinal symptoms during the interictal period in order to eliminate the group that overlaps with FD.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, migraine patients during the interictal period, had delayed gastric stasis compared with during the ictal period 21. However, previous studies had the limitation of not evaluating gastrointestinal symptoms during the interictal period and thus showed controversial results 20-22. Therefore, in our study we enrolled subjects with migraine without gastrointestinal symptoms during the interictal period in order to eliminate the group that overlaps with FD.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to migraineurs, subject with FD had more delayed gastric emptying [56]. However, a study evaluating liquid-phase gastric emptying observed delayed ictal but not interictal gastric emptying in migraineurs compared to controls [57].…”
Section: Migraine and Gi Disordersmentioning
confidence: 97%
“…Patients with migraine retain orally administered medication in their stomach, limiting passage into the small intestine, and its subsequent detection in serum, consistent with IG. [21][22][23] The etiology of gastroparesis in patients with migraine is unclear. 15,16 However, similar findings have been reported with the administration of paracetamol and tolfenamic acid.…”
Section: Introductionmentioning
confidence: 99%